Histopathological findings in the landscape of IgG4‐related pathology in patients with pituitary dysfunction: Review of six cases. (21st February 2021) - Vasaitis, Lilian; Wikström, Johan; Ahlström, Sengul; Gudjonsson, Olafur; Kumlien, Eva; Edén Engström, Britt; Casar‐Borota, Olivera
Abstract: IgG4‐related hypophysitis (IgG4‐RH) is increasingly being reported as an isolated entity or, less frequently, as a manifestation of a multiorgan IgG4‐related disease (IgG4‐RD), in which typical histopathology is a cornerstone for the diagnosis. We aimed to describe the histopathological changes in the surgical specimens from patients with clinical signs of pituitary disease that fulfilled the current diagnostic criteria for IgG4‐RH. Histopathological features were correlated with clinical and radiological findings. Of 19 patients with pituitary dysfunction and inflammatory changes in the surgical pituitary specimen operated on during 2011‐2019, we identified five patients with typical IgG4‐related pathology (lymphoplasmacytic infiltration with more than 10 IgG4‐positive plasma cells per one high power microscopic field, representing at least 40% of all plasma cells and at least focal storiform fibrosis). One patient with diabetes insipidus and pachymeningitis with IgG4‐related changes in a biopsy from the dura was also included. Additional histopathological changes that typically are not part of the IgG4‐RH were observed: Rathke's cleft cyst in four and granulomatous changes in two patients. One patient had an elevated serum IgG4 level and systemic manifestations that could be associated with the systemic IgG4‐RD. Our findings indicate that pure IgG4‐RH is uncommon. All patients with pituitary dysfunction, beyond typical IgG4‐related pathology, had other pathological findings that could trigger the secondary IgG4‐response. Both primary pathology and secondary IgG4‐related features should be reported in patients with pituitary dysfunction because their co‐occurrence may cause atypical clinical and imaging features, and unexpected response to surgical and pharmacological treatment. The current criteria for the diagnosis of IgG4‐RH can lead to overdiagnosis of IgG4‐RH if additional pathological changes are not taken into consideration. The classification criteria of IgG4‐RD proposed by the American College of Rheumatology/European League Against Rheumatism could help classify patients more properly as IgG4‐RH if applied to the pituitary gland.